Meta Analysis: The Effects of Parental Smokers, Peer Smokers, and Stress on Smoking Behavior in Teenagers - Riya Ulin Nuha; Argyo Demartoto; Hanung Prasetya (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: The habit of smoking is one of the health problems that the world is still facing today. The habit of smoking generally starts from youth, where it can have an impact on the health and cognitive behavior of adolescents that is sustainable. This study aims to estimate the influence of smoking parents, close friends of smokers, and stress on smoking habits in adolescents based on values obtained from several previous similar studies. Subjects and Method: This study used a systematic review study design and meta-analysis. The primary articles used were obtained from online databases (Google Scholar, Elsevier, PubMed, Springer Link, and Science Direct) published in 2012-2022. Population: teenagers. Intervention: parents of smokers, close friends of smokers, and stress. Comparison: parents don't smoke, close friends don't smoke, and don't get stressed. Outcome: smoking habit. In searching for primary articles, the researcher used the keywords “parents smoking” AND “peers smoking OR friends smoking” AND “stress” AND “adolescents OR youth” AND “smoking behavior” AND “cross-sectional study”. This study uses full text articles with a cross-sectional study design and contains aOR (adjusted odds ratio) values. The selection of articles is done using PRISMA flow diagrams. Primary article analysis using the Review Manager 5.4 application. Results: Articles with a sample size of 378,135 from Finland, Saudi Arabia, Brazil, Nigeria, South Korea, Taiwan, Malaysia, Turkey, Nepal, Ethiopia, Iran, Tunisia, France and Spain were selected for this meta-analysis. This study showed that adolescents whose parents smoked (aOR = 2.18; 95% CI = 2.12 to 2.25; p< 0.001), close friends smoked (aOR = 6.09; 95% CI = 2.71 to 13.70; p< 0.001), and stress significantly increased smoking behavior in adolescents (aOR = 1.41; 95% CI = 1.33 to 1.49; p< 0.001). Conclusion: Parents of smokers, close friends of smokers, and stress may all increase the risk of smoking. Keywords: parents, close friends, stress, smoking, teenagers. Correspondence: Riya Ulin Nuha. Master’s Program, Universitas Sebelas Maret. Jl. Ir Suratmi No.36A, Jebres, Jebres, 57126 Surakarta, Central Java, Indonesia. Email: ulin514@gmail.com. Telepon: +6281238710748.